Intra-familiar homicides: From 2006 to 2021 in the judicial district of Milan. (January 2023) - Vignali, Giulia; Blandino, Alberto; Rossetto, Ilaria; Merzagora, Isabella
Abstract: Introduction: The present research aims at analyzing criminological and medico-legal characteristics of intra-familiar homicides occurred in two major Italian cities (Milano and Monza) from the beginning of 2006 to the end of 2021. Methods: Cases were identified using the Institutional database of the Institute of Legal Medicine of Milan, where all the autopsies of victims were performed. Data about these cases were obtained from autopsies findings, preliminary investigation reports, local papers and victim relatives' interviews. In this period 11, 480 autopsies were performed: 392 were homicides and, among these, 94 were confirmed as intra-familiar homicides (as a result of 84 events). Cases were classified according to the classic definition of intimate partner violence (referring only to an intra-familiar context), parricides, filicides, fratricides, familicides and grannicides. Age, sex, nationality and risk factors of the victims and perpetrators, as well as methods of murder were registered for each case. Only in some cases, motives for murder were known. Results: The most frequent type of intra-familiar homicides was intimate partner violence (41.5%), followed by parricides (16%, mainly matricides), filicides (10.7%) and fratricides (6.4%). 9.6% of the total number of events were familicides. Risk factors were frequently involved, in particular among perpetrators and in the group of parricides, while among siblicides they showed minimal relevance. Overall, psychiatric pathologies were the main risk factors involved (at least 23.8%), unlike extrafamiliar homicides, where previous criminal report or involvement in illicit traffics are frequently reported among perpetrators. This finding enlightens the difficulties of caring for a relative with a mental disorder, who can become dangerous for the domestic caregiver. Furthermore, the high number of physical illness and the advanced age of victims points out the tragical consequences of the lack of social support system for these categories of people. Methods: of murder were mainly cold steel (30–31.9%) and firearms (21–22.3%). However choking/manual ligature (9–9.6%), blunt force trauma inflicted using objects found on the scenario or bare handed (16–17%) and combined methods (11–11.7%) were frequently represented confirming the expected high level of impulsivity related to this kind of crime. Highlights: Intimate partner violence remains the most common type of intra-familiar homicide. Criminological risk factors are often involved in intrafamiliar homicides, especially for some subgroups (parricides). Psychiatric anamnesis is the most relevant Risk factor, differently than among extrafamiliar murderers. Methods of murder reflect the high level of impulsivity of these crimes.